Multi-institutional Comparison of Intensity Modulated Photon Versus Proton Radiation Therapy in the Management of Squamous Cell Carcinoma of the Anus - Jahan J. Mohiuddin, MD; Krishan R. Jethwa, MD; Nikhil Grandhi, BS; William G. Breen, MD; Xingmei Wang, MS; Akbar Anvari, PhD; Hui Lin, PhD; Harigopal Sandhyavenu, MBBS; Abigail Doucette, MPH; John P. Plastaras, MD, PhD; William G. Rule, MD; James M. Metz, MD; et al. (Advances in Radiation Oncology, 2021)
Purpose: Concurrent chemoradiation therapy is a curative treatment for squamous cell carcinoma of the anus, but patients can suffer from significant treatment-related toxicities. This study was undertaken to determine whether intensity modulated proton therapy (IMPT) is associated with less acute toxicity than intensity modulated radiation therapy (IMRT) using photons. Materials and Methods: We performed a multi-institutional retrospective study comparing toxicity and oncologic outcomes of IMRT versus IMPT. Patients with stage I-IV (for positive infrarenal para-aortic or common iliac nodes only) squamous cell carcinoma of the anus, as defined by the American Joint Committee on Cancer's AJCC Staging Manual, eighth edition, were included. Patients with nonsquamous histology or mixed IMPT and IMRT treatment courses were excluded. Acute nonhematologic toxicities, per the National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE), version 4, were recorded prospectively at all sites. Acute and late toxicities, dose metrics, and oncologic outcomes were compared between IMRT and IMPT using univariable and multivariable statistical methods. To improve the robustness of our analysis, we also analyzed the data using propensity score weighting methods. Results: A total of 208 patients were treated with either IMPT (58 patients) or IMRT (150 patients). Of the 208 total patients, 13% had stage I disease, 36% stage II, 50% stage III, and 1% stage IV. IMPT reduced the volume of normal tissue receiving low-dose radiation but not high-dose radiation to bladder and bowel. There was no significant difference between treatment groups in overall grade 3 or greater acute toxicity (IMRT, 68%; IMPT, 67%; P = .96) or 2-year overall grade 3 or greater late toxicity (IMRT, 3.5%; IMPT, 1.8%; P = .88). There was no significant difference in 2-year progression-free survival (hazard ratio, 0.8; 95% CI, 0.3-2.0). Conclusions: Despite reducing the volume of normal tissue receiving low-dose radiation, IMPT was not associated with decreased grade 3 or greater acute toxicity as measured by CTCAE. Additional follow-up is needed to assess whether important differences arise in late toxicities and if further prospective evaluation is warranted.